Inhibition of MicroRNA-92 alleviates atherogenesis by regulation of macrophage polarization through targeting KLF4. Issue 3 (March 2022) - Gao, Feng; Chen, Xueying; Xu, Banglong; Luo, Zhidan; Liang, Yi; Fang, Sihua; Li, Mengli; Wang, Xiaochen; Lin, Xianhe
Highlights: MiR-92 inhibition promoted macrophage polarization to M2 state in vitro and in vivo. MiR-92 knockdown alleviated plaque size and increased stability. KLF4 was required for miR-92 silencing-mediated macrophage polarization. Abstract: Background: Atherosclerosis is a chronic inflammatory disease in which macrophage polarization plays an important role in contribution to atherosclerotic plaque formation and stability. Here we tested the effect of miR-92 regulation on the development of atherosclerosis beyond tumorigenesis and explored the potential mechanism. Methods and results: In the present study, bone marrow derived macrophages (BMDMs), mouse peritoneal macrophages (MPMs), and human macrophages were used to test the expression of miR-92. Here we noticed miR-92 levels were enhanced in classic M1 macrophage but decreased in alternative M2 macrophage, respectively. In vitro, we demonstrated that macrophages transfected with miR-92 inhibitor attenuated proinflammatory cytokine secretion represented by polarized M1 markers but promoted anti-inflammatory state that was indicative of an M2 phenotype. Mechanistically, miR-92 was found to directly interact with KLF4 and we further identified a requirement role of KLF4 in mediating the effect of miR-92 silencing macrophage polarization. Concomitantly, miR-92 inhibition treated ApoE −/− mice promoted macrophage polarization toward alternative M2 macrophage, thus protecting against atherosclerotic plaque formation and preventing a vulnerable phenotype. Conclusion: miR-92 inhibition promoted alternative macrophage activation and attenuated atherosclerosis regression partially regulated in a KLF4-dependent manner, which indicated that miR-92/KLF4 axis may serve as a promising strategy for prevention of atherosclerotic diseases. Graphical abstract: We showed herein that miR-92 contributed to the development of atherosclerosis by directly controlling macrophage polarization. Inhibition of miR-92 downregulated markers that represent classical activated macrophages but increased alternative activated macrophages markers. Moreover, miR-92 inhibitor treated ApoE-/- mice fed with HFD leaded to alleviated atherosclerotic plaque size and increased stability characterizes. Mechanistically, miR-92 can directly target KLF4 which was required for the macrophage polarization mediated by miR-92 silencing. Image, graphical abstract